Abnormal steroidogenesis and aromatase activity in preeclampsia. (September 2018) - Berkane, Nadia; Liere, Philippe; Lefevre, Guillaume; Alfaidy, Nadia; Nahed, Roland Abi; Vincent, Jessica; Oudinet, Jean-Paul; Pianos, Antoine; Cambourg, Annie; Rozenberg, Patrick; Galichon, Pierre; Rousseau, Alexandra; et al.
Abstract: Introduction: Estrogens and progesterone play critical roles in angiogenesis and vasodilation. Moreover, placental aromatase deficiency is detected in women with preeclampsia (PE) at delivery. We hypothesized that abnormal steroidogenesis occurs much earlier than typical PE diagnosis. Thus, we investigated whether the circulating steroid profile was already disturbed at 24–29 weeks of gestation in women with subsequent PE, and compared the profile with that of women with "placental" small gestational age (SGA) without PE. Methods: We selected nulliparous women (n = 90) from the MOMA trial, including women with PE (n = 25), SGA (n = 25), and controls (NP; n = 40), for plasma steroid profiling by gas chromatography/mass spectrometry and to measure placental growth factor and soluble fms-like tyrosine kinase-1. Placental aromatase expression was evaluated in a new set of women. Results: Compared with that of controls, the women with PE had a significantly lower estrone/androstenedione ratio, and exhibited a decreasing trend for estradiol and estrone levels. Lower estriol levels were observed in the SGA group compared to the NP group. Compared with that of controls, the women with PE and SGA had significantly higher levels of 20α-dihydroprogesterone (20α-DHP) and 20α-DHP/progesterone ratios. Pregnenolone sulfate levels were lower in the PE group than in the NP and SGA groups. Decreased expression of aromatase was observed in the PE group compared to the control group. Discussion: Preeclampsia appears to be characterized by specific steroidogenesis dysregulation long before PE diagnosis, highlighting potential new biomarkers of PE. Highlights: Abnormal steroidogenesis occurs long before clinical signs of preeclampsia (PE). Preeclamptic women had a specific aromatase defect at 24–29 weeks of gestation. Preeclamptic women had lower placental aromatase expression at delivery. Pregnancies with PE and "placental" SGA had increased 20α-dihydroprogesterone levels. Pregnancies with "placental" SGA are associated with low estriol levels.